The 3rd International Conference on African Digital Libraries and Archives Digital Libraries and Archives in Africa: Changing Lives and Building Communities - Al Akhawayn University (Al Akhawayn University in Ifrane, Morocco, 2016)
The corpus of Moroccan manuscripts is estimated at more than 80,000 titles and 200,000 volumes held at a number of public and private libraries—mostly religious institutions and zawāyā. These collections are invaluable both as repositories of human knowledge and memory and for their aesthetic value in terms of calligraphy, illumination, iconography and craftsmanship. Several medieval authors position Morocco as an important center in the Muslim West (al-Gharb al-Islami) for manuscript production, illumination, binding and exchange. However, except for a few scattered publications, a history of North African Arabic calligraphy (al-khatt al-maghribi) remains to be written. By providing the tools for making these collections readily accessible to the scholarly community in the Maghrib and beyond, ICT will make possible the study of North African scripts within the broader context of Arabic calligraphy and the Islamic arts of the book in general. The two main manuscript collections in Morocco are hosted at the National Library of Morocco (Bibliothèque nationale du royaume du Maroc, or BNRM, formerly General Library and Archive) in Rabat (12,140 titles), and the Qarawiyyin Library in Fez (5,600 titles, 3,157 of which in several volumes). Theses collections originated mostly from waqf (pious endowments) and state appropriation of private collections (e.g., 1,311 and 3,371 titles from the al-Glawi and al-Kattani collections respectively). They are written almost entirely in Arabic and in various scripts; Amazigh (Berber) manuscripts in Arabic script and Hebrew manuscripts constitute less than one percent of the total collections.